K-Means Cluster for Seismicity Partitioning and Geological Structure Interpretation, with Application to the Yongshaba Mine (China) - Xueyi Shang; Xibing Li; A. Morales-Esteban; Longjun Dong; Kang Peng (Shock and Vibration)
Seismicity partitioning is an important step in geological structure interpretation and seismic hazard assessment. In this paper, seismic event location (X,Y,Z) and Euclidean distance were selected as the K-Means cluster, the Gaussian mixture model (GMM), and the self-organizing maps (SOM) input features and cluster determination measurement, respectively, and 1516 seismic events (M>-1.5) obtained from the Yongshaba mine (China) were chosen for the cluster analysis. In addition, a Silhouette and Krzanowski-Lai- (KL-) combined S-KL index was proposed to obtain the possible optimum cluster number and to compare the cluster methods. Results show that the K-Means cluster obtains the best cluster “quality” with higher S-KL indexes on the whole and meaningful clusters. Furthermore, the optimal number for detailed geological structure interpretation is confirmed as eleven clusters, and we found that two areas probably have faults or caves, and two faults may be falsely inferred by mine geologists. Seismic hazard assessment shows that C5 and C7 (K=11) have a high mean moment magnitude (mM) and C1, C2, C3, and C4 (K=11) have a relatively high mM, where special attention is needed when mining. In addition, C7 (K=11) is the most shear-related area with a mean S-wave to P-wave energy ratio (mEs/Ep) of 41.21. In conclusion, the K-Means cluster provides an effective way for mine seismicity partitioning, geological structure interpretation, and seismic hazard assessment.